Pharmaceutical Innovations Using Nano-Technology for Advanced Drug Delivery Systems - Zufi Shad; Iqra Haider; Hadia Naz; M. Ubaid Akram; M. Anas (RADS Journal of Biological Research & Applied Science)
Introduction: Nanotechnology is about employing materials and devices at a tiny scale, involving their design, creation, analysis, and use. In pharmaceutical sciences, nanotechnology involves the manipulation of materials at the nanoscale to create precise drug delivery systems that interact with biological systems at the molecular level.